Dynamic imaging of oil shale pyrolysis using synchrotron X‐ray microtomography. Issue 13 (2nd July 2016) - Saif, Tarik; Lin, Qingyang; Singh, Kamaljit; Bijeljic, Branko; Blunt, Martin J.
Abstract: The structure and connectivity of the pore space during the pyrolysis of oil shales determines hydrocarbon flow behavior and ultimate recovery. We image the time evolution of the pore and microfracture networks during oil shale pyrolysis using synchrotron X‐ray microtomography. Immature Green River (Mahogany Zone) shale samples were thermally matured under vacuum conditions at temperatures up to 500°C while being periodically imaged with a 2 µm voxel size. The structural transformation of both organic‐rich and organic‐lean layers within the shale was quantified. The images reveal a dramatic change in porosity accompanying pyrolysis between 390 and 400°C with the formation of micron‐scale heterogeneous pores. With a further increase in temperature, the pores steadily expand resulting in connected microfracture networks that predominantly develop along the kerogen‐rich laminations. Key Points: Dynamic oil shale imaging under pyrolysis conditions is performed using synchrotron X‐ray microtomography 3‐D visualization and quantification of the pore space is performed as a function of temperature and time in organic‐rich and organic‐lean regions Microscale disconnected pores are first observed at 390 degrees Celsius; the porosity increases dramatically between 390 and 400 degrees Celsius and becomes connected